Comparison of Interleukin-1β Levels In Open and Closed Fracture Patients of The Long Bone In Padang - Iqbal Arnif; Roni Eka Sahputra; Hendra Maska (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background and Purpose. Trauma is a significant burden on causes of death, disability, and financing in least developed or "third world" countries. Fracture healing, especially in wounds and tissues, begins with a hemostatic and inflammatory phase triggered by inflammatory mediators such as cytokines, particularly IL-1β and TNF-. The purpose of this study was to determine the difference in levels of interleukin-1β in open and closed fractures of long bones in PadangMethod. This type of research is analytic observational with cross sectional design with primary data. The data were taken from the examination of IL-1β levels in long bone fracture patients at RSUP Dr. M. Djamil, RSKB Ropanasuro and RST Reksodiwiryo Padang for 4 months starting from March 2021 to July 2021. The sampling technique in this study used non-probability sampling with the consecutive sampling method. The analysis was carried out using the Independent sample T-Test to see the difference in mean IL-1 which would be calculated for open fractures and closed fractures of long bones.Results. The results showed that most (92.9%) of the patients were male, 50% had open fractures, and 50% closed fractures. The mean value of the patient's age was 34 years and the mean level of IL-1β was 555,951 pq/L. Most of the fracture sites in patients were tibia and fibula (35.7%) and femur (35.7%) and 28.6% were radius and ulna. The results showed that there was a significant difference in the mean levels of IL-1β in patients with open and closed fractures of long bones (p-value = 0.007)Conclusion. There are differences in the levels of interleukin-1β in open and closed fractures of long bones in Padang. This research is expected to provide consideration to support examinations in health services, in this case in fracture patients